Analysis of the performance of the General Secretariat with the Ballance Scorecard approach at the Ministry of Home Affairs - Azizah, Siti Nur; Rahayu, Amy Yayuk (International Journal of Social Service and Research, 2024)
Efficient and effective governance is critical to ensuring good public services and achieving development goals. The Secretariat General is a very crucial part of every ministry that is responsible for supporting the management and administration of the ministry. The purpose of this study is to analyze the performance of the Secretariat General of the Ministry of Home Affairs using the Balance Scorecard approach. This research uses qualitative research methods. Research data were obtained through interviews, observations, and documentation. The data obtained was then analyzed with the Balance Scorecard. The results showed significant improvements in the performance of the General Secretariat. The financial aspect shows positive growth in financial and asset management. From a customer perspective, service to stakeholders has improved. The internal process aspect recorded improvements in operational efficiency and productivity. Finally, from a growth and learning perspective, employee training and development initiatives and the application of information technology have strengthened organizational capacity.